The Effect of Islamic Education on the Religiousness And Social Participation of The Community of Ay Banda Neira Island - Muhammad Aldi; Retisfa Khairanis; Akhmad Nurul Kawakip; Sulthan Al Aziz (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2026)
This study aims to analyze the influence of Islamic education measured through the intensity of formal madrasah activities and non-formal majelis taklim activities on religiosity as indicated by ritual practices and the internalization of values and social participation as indicated by mutual aid and social concern among the residents of Ay Island, Banda Neira. The response to modernization serves as the backdrop for this study in this island region with limited access. Using a quantitative correlational approach, the sample was selected through proportional random sampling, comprising 100 respondents including religious leaders, educators, and the general public across all ages and genders. Questionnaire data were analyzed using multiple linear regression. Statistical test results indicate that Islamic education has a positive and significant effect on religiosity R² = 0.465, p = 0.000 and social participation R² = 0.374, p = 0.003. Simultaneously, the two variables contributed 54% F = 15.284, p = 0.000 to social participation, with no significant differences in influence found among the respondents’ professional groups. These findings confirm that Islamic education serves as a foundation for strengthening social solidarity. Nevertheless, this study has limitations regarding generalizability because it focuses on only one island, has not explored local cultural and economic factors, and is susceptible to social desirability bias regarding issues of religiosity. It is recommended that local governments develop policies to strengthen non-formal institutions, and it is suggested that future researchers use qualitative or longitudinal approaches to explore the underlying causes and the subjective motivations of the community.